Pemenuhan Kebutuhan Psikologis Dasar sebagai Mediator antara Dukungan Dosen dan Academic Buoyancy - Rohinsa, Meilani; Maria Yuni Megarini; Trisa Genia Zega (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
While adapting to the hybrid learning system, students often encounter various obstacles. It takes the ability to overcome it, or what is known as academic buoyancy. This study aims to analyze the role of essential psychological fulfillment as a mediator in the relationship between lecturer support and student academic buoyancy when carrying out hybrid learning. This type of research is quantitative research using an explanatory research approach. Data was collected through survey techniques carried out online using a Google form for two weeks. This study uses statistical analysis of mediation using the Heyes Process Macro. The results of the mediation analysis of 115 participants show that fulfillment of basic psychological needs partially mediates the relationship between lecturer support and academic buoyancy. Lecturer support is proven to have a direct influence on academic buoyancy. Partial mediation also shows that the fulfillment of basic psychological needs is also confirmed to play a psychological factor in explaining how lecturer support can affect academic buoyancy. Completion of these psychological needs will then affect the increase in academic buoyancy. It was concluded that the role of fulfilling basic psychological needs in bridging the relationship between lecturer support and academic buoyancy. Therefore, the implication of this research is the development of interventions with the target of manipulating support from lecturers to meet students' basic psychological needs.